2020
DOI: 10.1021/acs.bioconjchem.9b00818
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Future of Nanomedicine to Impact Patients: An Analysis of US Federal Funding and Interventional Clinical Trials

Abstract: The US and governments around the world, and companies, have made a considerable investment in nanomedicine, and there have been important discoveries. Nevertheless, there has been considerable debate as to whether the investment, both in money and in time, has been worth it. That question is not yet definitively answerable. However, investigators (and investors) might also wonder if the efforts in nanomedicine are likely to continue at the same pace as over the past decade. For this paper, an analysis was don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…199 Abraxane, a nanoscale albumin-bound paclitaxel, was the first protein-based nanotherapeutic approved by the FDA in 2005 to treat metastatic breast cancer and then, for nonsmall cell lung and pancreatic cancers. 197 In addition to albumin, other proteins such as gelatin, zein, and milk proteins of βlactoglobulin and casein have also been approved by the FDA for pharmaceutical and biomedical applications. 163 Ontak, a recombinant fusion protein of diphtheria toxin and interleukin-2, is one of the first actively targeted therapeutic nanoplatforms approved by the FDA to treat cutaneous T cell lymphoma cells.…”
Section: Cancer Nanomedicines On the Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…199 Abraxane, a nanoscale albumin-bound paclitaxel, was the first protein-based nanotherapeutic approved by the FDA in 2005 to treat metastatic breast cancer and then, for nonsmall cell lung and pancreatic cancers. 197 In addition to albumin, other proteins such as gelatin, zein, and milk proteins of βlactoglobulin and casein have also been approved by the FDA for pharmaceutical and biomedical applications. 163 Ontak, a recombinant fusion protein of diphtheria toxin and interleukin-2, is one of the first actively targeted therapeutic nanoplatforms approved by the FDA to treat cutaneous T cell lymphoma cells.…”
Section: Cancer Nanomedicines On the Marketmentioning
confidence: 99%
“…Nanoscale drugs and nanomaterials integrated therapeutics have been increasingly considered over the last two decades in the pharmaceutical industry . These nanobased products have been extensively reviewed in some recent reports. As mentioned in the previous sections, some FDA-approved drug delivery nanosystems are currently used to treat various diseases. Cancer is the main focus of studies, and the liposomal nanoformulations are of great interest for this aim.…”
Section: Cancer Nanomedicines On the Marketmentioning
confidence: 99%
“…Currently, there are several anticancer nanomedicines approved by the U.S. Food and Drug Administration (FDA), such as Doxil (doxorubicin liposomes), DaunoXome (daunorubicin liposomes) and Abraxane (paclitaxel albumin-bound nanoparticles) 24 , 25 , 26 , 27 . A list of nanomedicines currently under clinical trial can be found in a recent published review 28 . However, the heterogeneity of tumors can lead to low therapeutic efficacy, acquired resistance and side effects 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promise of nanoencapsulated delivery, nanotherapeutics have overall been far less successful in the clinic than originally hypothesized. [ 8–11 ] Discouragingly, understanding the mechanisms of failure has been challenging. Foremost, the pharmacokinetics of nanomaterial in vivo is complicated and difficult to predict.…”
Section: Introductionmentioning
confidence: 99%